Pengaruh Peran PR terhadap Reputasi Perusahaan Operator Selular (Prologia, 2019)
Reputation is something that cannot be seen but can be felt, having a good reputation is the main goal that every company wants to achieve. Therefore, researchers discuss the influence of the role of PR on Telkomsel's corporate reputation. According to Charles J. Fombrun (2016) stated that there are four aspects that create a company's reputation, namely credibility, reliability, trustworthiness, responsibility. (p.48) Whereas the measurement of the role of public relations was adopted from the dimensions proposed by Cutlip (2009, p.45) including communication technicians, expert prescriber, communication facilitators and problem solving facilitators. This research methodology is quantitative by distributing 100 questionnaires to Telkomsel users. From this study, the results of linear regression Y = 6.081 + 0.808 X, and a significance value of 0,000